Effects of dry needling in the treatment of trigger points in cervical spine myofascial pain syndrome: a systematic review of randomized clinical trials (Research, Society and Development, 2021)
Myofascial pain syndrome is one of the most common causes of musculoskeletal pain and disability, affecting an age group between 31 and 50 years, being more favorable in people who perform repetitive movements and more frequently in the cervical region and shoulder girdle. The exact etiology of myofascial pain syndrome is not fully defined, but its treatment is focused on decreasing pain, improving muscle strength and providing good posture. Dry needling is a minimally invasive procedure, aiming to reduce myofascial pain by placing a needle directly over the trigger point, aiming to reduce local pain, in addition to restoring range of motion. A systematic review of randomized clinical trials was carried out, aiming to identify the benefits of dry needling in the cervical spine for patients with myofascial pain syndrome through a literature review. The following databases were used: PEDro, ScieLo and Pubmed, in Portuguese and English between 2016 and 2021. A total of 552 studies were obtained, after crossing the descriptors and applying the inclusion and exclusion criteria, 10 articles were selected. Dry needling is a valuable treatment for patients with myofascial pain syndrome in the cervical spine, improving pain. However, the combination of other techniques produces muscle relaxation, range of motion of the cervical muscles, reflecting on the quality of life of these patients.